Reception of Law Worship:The Experiences of Muslims Worship During Pandemic Covid-19 - Fernando, Henky; Abdullah, Irwan; Yusuf, Mohamad (Nurani, 2022)
The reception of law worship during the pandemic Covid-19 is a pattern that is very important to reflect on as a lesson learned after the Covid-19 pandemic. This study, in addition to providing a conceptual understanding of Muslim religious law receptions pattern during the pandemic Covid-19, also to reflects this reception contextually. This study uses a qualitative descriptive approach. Data collection was carried out through an interview process with Muslims who actively carried out worship activities in the congregation during the pandemic Covid-19 at the Kotagede Mataram Gede Mosque. The analysis in this study was carried out through the process of reducing, describing, and inductively interpreting the data, to obtain a classification and conclusion regarding Muslim religious law reception pattern. This study found that the Muslim worship law reception pattern during the pandemic Covid-19 was not least carried out through three contexts, namely; reception in the context of adaptation, reception in the context of negotiation, and reception in the context of resistance. This study also recommends the importance of comparing Muslim worship law reception patterns in a more macro context.